Accelerated aging and electrical conductivity tests in crambe seeds - Pereira Lima, Juliana Joice [UNESP] (2015)
The aim of this study was to adapt the methodology of the accelerated aging and electrical conductivity tests for determination of physiological potential in crambe seeds. Six seed lots of crambe (cv. FMS Brilhante) were subjected to determination of moisture content, germination test, first count germination, emergence, and emergence speed index. For the accelerated aging test, the traditional methodology was used with water, and with a saturated potassium chloride and sodium chloride solution in three periods of exposure (24, 48, and 72 hours) at 41°C; the electrical conductivity test was performed with four pre-soaking treatments (0, 2, 4, and 8 hours) and four soaking periods (4, 8, 16, and 24 hours) at 25°C. The accelerated aging test with water for 72 hours and the electrical conductivity test with 2 hours of pre-soaking and assessment after 16 hours were effective for classification of the crambe seed lots in regard to physiological quality.